Um estudo sobre os topônimos de etimologia não tupi no município de Inhangapi-PA - COLARES, Eluanne Alessandra de Azevedo (2020)
This work presents a study about analysis of the place names of etymology not tupi of municipality of Inhangapi-Pa, having as object of study the communities of the municipality. To this end, it is proposed as a general goal is to analyze the place names of etymology not tupi naming communities of the municipality of Inhangapi-Pa, located north of the municipality of Marikina city. And as specific objectives: the aim is to describe the etymology of place names of origin not tupi of municipality of InhangapiPa, taking into consideration the etymological dictionaries of Bechara (2011); Wedge (2010); Guerios (1973) and Axe (1984). Present the morphological description of place names and sort the designativos searched according to taxeonômica classification suggested by Dick (1990). The work is based on theoretical perspective of Dick (1990) and in jobs surveyed which follow the same line of research in the area of theoreticalmethodological research locative, as Andrade (2006), Dargel and Ri ... This work presents a study about analysis of the place names of etymology not tupi of municipality of Inhangapi-Pa, having as object of study the communities of the municipality. To this end, it is proposed as a general goal is to analyze the place names of etymology not tupi naming communities of the municipality of Inhangapi-Pa, located north of the municipality of Marikina city. And as specific objectives: the aim is to describe the etymology of place names of origin not tupi of municipality of InhangapiPa, taking into consideration the etymological dictionaries of Bechara (2011); Wedge (2010); Guerios (1973) and Axe (1984). Present the morphological description of place names and sort the designativos searched according to taxeonômica classification suggested by Dick (1990). The work is based on theoretical perspective of Dick (1990) and in jobs surveyed which follow the same line of research in the area of theoreticalmethodological research locative, as Andrade (2006), Dargel and Ri ... among others. For the development of the work, were followed a few steps, namely: a) the identification and selection of the object of study; b) etymological analysis; c) structural analysis and d) rating locative, anchored in the draft Dick (1990). From the searchresults, the morphological structure more applicant was composed of 20 place names. When it comes to taxeonômica classification, the most productive tax was hodotopônimo, having semantic relationship communication routes rural or urban, Anthropo-cultural nature. This shows that the culture of the local man, was the basis for the naming of such communities Act.